Impact of irrigation and micronutrient treatments on insect herbivore population dynamics in soybean - Debnath, Rahul; George, Justin; Bhandari, Ammar B.; Kariyat, Rupesh; Reddy, Gadi V. P.; Glover, James P.; Kharel, Tulsi P.; Reddy, Krishna N. (Frontiers in Agronomy, 2025)
Soybean production is substantially affected by insect pests, necessitating the implementation of appropriate management strategies. Effective irrigation and fertilizer regimes have been found to affect pest populations in agroecosystems. However, their interactive effects on herbivore incidence are less understood. This study reports the abundance and diversity of insect pests, especially hemipteran, lepidopteran, and stink bug species complexes, encountered on soybeans throughout their vegetative and reproductive growth stages under varying irrigation and micronutrient treatments. First, we compared total and major insect pest population densities in irrigated and rainfed conditions. Afterwards, we evaluated how the frequency of insect pests on soybean was influenced by the foliar application of various micronutrients (Fe, Zn, and Fe + Zn) compared to the control plots. This field experiment was repeated over two growing seasons, during 2023 and 2024. Results showed that total insect pest populations were significantly higher (p<0.001) in control plots than in plots treated with the combined micronutrients (Fe + Zn). However, compared to rainfed treatment, irrigated soybean attracted significantly more insect herbivores. Furthermore, micronutrients had no significant impact on reducing pest pressure when applied in conjunction with irrigation. These findings indicated that micronutrients and irrigation can have complex effects on plant-insect interactions, and the specific effects may depend on particular nutrients, crop species, and water availability. These findings also provide evidence that combining foliar applications of ferrous and zinc in soybean fields can efficiently decrease insect pest populations independent of irrigation.